A typology of net-enabled organisational capabilities for digital competitive advantage: the case study of travel and hospitality industry in China. (1st January 2013) - Zhu, Zhen; Zhao, Jing; Jin, Xin
Electronic business (e-business) is evolving from its technological tool towards a strategic role, and supporting new business strategies. Prior studies explained e-business value creation from net-enabled organisational capability (NEOC) perspective, and delivered many insights at firm level with individual-level analysis. In this paper, we posit that digital competitive advantage will be dependent upon the deployment of multiple types of NEOCs and their appropriate portfolio. Further, we use Wade and Hulland's (2004) capabilities taxonomies and multiple case-based data in the Chinese travel and hospitality industry to understand the effect of multiple types of NEOCs on competitive advantage. Research finds a series of key NEOCs in four cases firms for understanding why these travel and hospitality firms can achieve successful e-business operations. Our research suggests that firms need to maintain capability portfolios of outside-in capabilities, spanning capabilities, and inside-out capabilities for gaining a specific business purpose instead of only focusing on certain IT capability.